The Impact of Globalization and The Free Market on The Economic Growth of Umkm on Pekalongan - Prasojo, Bahtiar Aji (Fakultas Ekonomi dan Bisnis, Universitas Palangka Raya (UPR), 2023)
Globalization and free markets have a big influence on the Indonesian economy, including MSMEs as the spearhead of the Indonesian economy today. Globalization is spreading rapidly through communication technology, changing many people's habits such as food, lifestyle, and even politics. The free market also presents new challenges because goods, services and labor will more easily enter other countries. People's markets and modern shops also support Pekalongan City's economic activities, which are largely driven by trade in superior goods such as batik and fisheries. The trade and cooperative sectors together make a significant contribution to the expansion of the economy in Pekalongan City. The commercial development of Pekalongan City's superior goods, such as batik, fish, weaving, convection, and several other crafts that develop with a wealth of invention and ingenuity, is proof of this. Free markets have advantages and disadvantages. The ability to easily obtain desired foreign goods and keep up with global market trends is a beneficial impact Globalization and free markets have had negative and positive impacts on MSMEs in Pekalongan, but on the other hand this also brings great opportunities for MSMEs in Pekalongan to further expand their market reach.